Renewable Energy from Pyrolysis of Pine Wood with Zeolite Catalyst - Zubaidi Achmad; Abdullah Kunta Arsa; Bety Alfitamara; Alfia Virgiandini (Eksergi, 2022)
Renewable energy becomes a hot issue on the decrease of fossil energy reserves that can not be renewed. To answer the challenge of the availability of these energy a study was performed in a high-temperature cracking process from pine wood to obtain fuel oil or so-called pyrolysis. The purpose of this study was to determine the yield, physical properties, and the calorific value of the pyrolysis results. Pyrolysis process is done by varying the percentage of mordenite-type zeolite catalyst as much as  0% b/b, 2% b/b, and 4% b/b, with a mass of 100 grams of pine wood that passes sieving each sample to 50 mesh. Before use, the catalysts physically activated by heating at a temperature of 500°C and chemically activated using HCl to enhance the activity of the zeolite. Pyrolysis carried out at 400°C, 450°C, 500°C, and 550°C. After the analysis, bio-oil obtained optimum yield of 43.77142% by mass of the catalyst 4% b/b and a temperature of 500 °C. Physical properties obtained in the form of density 1.094723 g/ml, 2.96 cP viscosity, and 58°C flash point. While the highest calorific value on the condition of the catalyst 4% and the reaction temperature 550°C is 26045.50 kJ/kg.